DESAIN PENGURANGAN LEAD TIME SIKLUS KONTAINER UNTUK MEMPERCEPAT PERPUTARAN STOK KONTAINER DI PT X - Roby Heryanto; I Nyoman Sutapa (Jurnal Titra, 2018)
The aim of this research is to analyze the lead time of container cycle for Surabaya-Banjarmasin-Surabaya route in PT. Salam Pacific Indonesia Lines (SPIL). For a single trip route, each container will go through at least 17 times of status displacement. Software Process Simulator is used to provide a comprehensive insight and depth understanding on the status displacement. It simulates the container’s status displacements through the whole process. The Pareto Chart of the simulation results indicates that the FXD (Full ex-discharge) status and FTL (Full to Load) status have a lot of room to be improved. The results of this study, suggests to increase the demurrage cost by 30% from the initial price so that the time needed for FXD status is not too long. Additionally, for the FTL status, the proposed solution ns are to exert weighing and reexamine on the container’s seal before the ‘Surat Penyerahan Container’ (SPC) is given to the administrator and to eliminate the “administator confirmation” activity from ship operation protocols. By the simulation the lead time of the whole process will reduce by 12.7 hours.